Pengaruh Gaya Kepemimpinan Situasional, Disiplin dan Motivasi Kerja Terhadap Produktivitas Karyawan PT. Pratama Sentosa Pemalang - Ignatius Soni Kurniawan; Ismi faghmilah; Jajuk Herawati (Universitas Batanghari, 2021)
This study aims to see the attitude of situational leadership style, discipline and work motivation partially on employee productivity. The population in this study were all employees at PT. Pratama Sentosa Pemalang with 52 respondents. Data were collected through a survey with a questionnaire instrument which was analyzed by multiple linear regression. The findings show that managerial needs to consider the aspects of situasional leadership, discipline, work motivation in encouraging employee productivity.